PESTEL ANALYSIS OF CHINESE MARITIME SILK ROAD TO INDONESIA IN REALIZING THE GLOBAL MARITIME FULCRUM - Zulham, Muhammad (Jurnal Pertahanan dan Bela Negara, 2026)
This research focuses on the relationship between Indonesia and China according to the policies of the Global Maritim Fulcrum (GMF) and China's Belt and Road Initiative through the Maritime Silk Road (MSR). BRI is China's step in realizing its dream called the Chinese Dream, is considered to be able to threaten Indonesia's sovereignty from political, economic, social to technological, environmental and legal (PESTEL). However, it is not only considered threatening, China's presence with its MSR program is considered to be a chance for Indonesia in realizing GMF. The various views on the perceived threats and benefits make researchers interested in discussing them from the PESTEL analysis level. This research uses PEST analysis theory, geopolitical theory, and defense management theory. This research uses a qualitative research method described by the PESTES approach. This research shows that the presence of China through MSR for Indonesia from the perspective of PESTEL raises various perceptions of benefits that can be felt by Indonesia. The perceived threat allows Indonesia to be hegemonized by China with the debt trap falling in the cooperation between the two countries in the proportion of GMF – MSR.